Keragaman Kualitas Buah pada Dua Varietas Okra (Abelmoschus esculentus L. Moench) dari Umur Panen Berbeda - Aplugi, Dewie Maria Agustien; Melati, Maya; Kurniawati, Ani; Faridah, dan Didah Nur (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Okra (Abelmoschus esculentus L. Moench) is a functional vegetables that has high economic value and it is usedas health purposes due to high bioactive compounds and dietary fiber contents. Okra pod is gradually harvested followsflowering time. The purpose of this study was to evaluate the effect of harvest age on Nitrogen (N), Phosphorus (P), Potassium(K), pigment and phenolic contents of two okra varities. The experiment was conducted from October 2017 to February 2018at IPB experimental station in Leuwikopo, Dramaga, Bogor. The experimental field is located at ± 185 m asl with 6033’49.3”S and 106043’30.7” E. The experiment used single factor, namely harvest time, in randomized complete block nested in factorof okra variety with 4 replicates. The varieties of okra were Zahira (red okra) and Naila (green okra), while harvest agesconsisted of 5, 7, 9, and 11 days after the anthesis (DAA). The results of the study showed significant effect of harvest age onN, P, anthocyanin and phenolic contents. Okra pod harvested at 5 DAA, had the highest N, P and anthocyanin levels; whilethe highest phenolic level was obtained from okra pod harvested at 7 DAA. There were interactions effect between harvesttime and okra varieties on chlorophyll and carotenoid contents. The red okra harvested at 5 DAA had the highest content oftotal chlorophyll (536.83 μg g-1) and carotenoid (147.79 μg g-1).